Proteção do óxido nítrico sobre o estresse oxidativo causado por herbicidas em arroz irrigado - Silva, Keli Souza da (2015)
Although selective, some herbicides cause injury in plants, resulting in uncontrolled production of reactive oxygen species. Nitric oxide (NO) is appointed as a reducer of the effects caused by oxidative stress in plants; however, their mitigation mechanisms are not yet clear. This study aimed to evaluate the nitric oxide protection mechanisms, provided by sodium nitroprusside (SNP), in the flooded rice cultivar Puitá INTA CL exposed to clomazone herbicide (360 g a.i. L-1), oxyfluorfen (240 g a.i. L-1), oxadiazon (250 g a.i. L-1) and the formulated mixture of paraquat (200 g a.i. L-1) + diuron (100 g a.i. L-1) in vitro and in vivo. For this purpose, (i) leaf segments were pre-incubated with 0, 200 and 2000 μM of SNP and exposed to five herbicides concentrations, and the protective effect confirmed by the NO scavenger, carboxyPTIO, (ii) seeds were soaked by one and 10 hours in solution containing 200 μM of SNP and after sowing, clomazone (1.7 and 3.4 L ha-1 of c.p.) was applied in the post-seeding and the needle stage (iii) plants were treated with 200 and 2000 μM of SNP and sprayed with 1.0 L ha-1 of herbicides oxadiazon, oxyfluorfen + diuron and paraquat. The concentration of 200 μM of SNP has reduced, up to 14% the electrolyte leakage in rice leaf segments exposed to 755.9 μM of oxadiazon, as well as, the imbibition of seeds with 200 μM of SNP for 10 hours increased by 33.1% the total content of chlorophyll, maintaining the pigmentation of seedlings exposed to 3.4 L h-1 of clomazone, applied to the needle stage. When sprayed on the shoot, paraquat + diuron, oxyfluorfen and oxadiazon, respectively, caused the ions leakage of 89.8; 62.8 and 18.3%, while the pre-treatment of the plants with 2000 μM of SNP decreased by 11 and 25.4% the damage caused by the first two, however, there was not reduction in injury caused by oxadiazon. The pre-treatment with SNP minimized the oxidative stress caused by herbicides, by the reducing in the hydrogen peroxide levels and TBARS and by the increase in the pigments levels, reflecting on the lower activity of the enzymes SOD and POD, however, such changes are dependent on the SNP concentration, exposure time and the level of stress caused by herbicides. In the absence or low levels of stress, NO was toxic to plants.